A Triple Gene-Deleted Pseudorabies Virus-Vectored Subunit PCV2b and CSFV Vaccine Protects Pigs against PCV2b Challenge and Induces Serum Neutralizing Antibody Response against CSFV - Selvaraj Pavulraj; Katrin Pannhorst; Rhett W. Stout; Daniel B. Paulsen; Mariano Carossino; Denise Meyer; Paul Becher; Shafiqul I. Chowdhury (Vaccines, 2022)
Porcine circovirus type 2 (PCV2) is endemic worldwide. PCV2 causes immunosuppressive infection. Co-infection of pigs with other swine viruses, such as pseudorabies virus (PRV) and classical swine fever virus (CSFV), have fatal outcomes, causing the swine industry significant economic losses in many if not all pig-producing countries. Currently available inactivated/modified-live/vectored vaccines against PCV2/CSFV/PRV have safety and efficacy limitations. To address these shortcomings, we have constructed a triple gene (thymidine kinase, glycoprotein E [gE], and gG)-deleted (PRVtmv) vaccine vector expressing chimeric PCV2b-capsid, CSFV-E2, and chimeric Erns-fused with bovine granulocytic monocyte-colony stimulating factor (Erns-GM-CSF), designated as PRVtmv+, a trivalent vaccine. Here we compared this vaccine’s immunogenicity and protective efficacy in pigs against wild-type PCV2b challenge with that of the inactivated Zoetis Fostera Gold PCV commercial vaccine. The live PRVtmv+ prototype trivalent subunit vaccine is safe and highly attenuated in pigs. Based on PCV2b-specific neutralizing antibody titers, viremia, viral load in lymphoid tissues, fecal-virus shedding, and leukocyte/lymphocyte count, the PRVtmv+ yielded better protection for vaccinated pigs than the commercial vaccine after the PCV2b challenge. Additionally, the PRVtmv+ vaccinated pigs generated low to moderate levels of CSFV-specific neutralizing antibodies.